2021
DOI: 10.1371/journal.pone.0257987
|View full text |Cite|
|
Sign up to set email alerts
|

Trade vulnerability assessment in the grain-importing countries: A case study of China

Abstract: Since the 2008 global food crisis, food security vulnerability has been a prominent topic in the food policy debate. However, vulnerability is inherently difficult to conceptualize and is more challenging to operationalize and measure. This study constructs a mathematical model and takes China as a case study to measure the vulnerability and sensitivity of China with its partners in the international grain trade. The results show that 1) the degree of interdependence between China and its grain trading partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This reflects the spatial scale dependence effect of international trade relations [54,55], i.e., that the influence of different levels of network cores is differentiated at the global and regional scales. The characteristics of geographical proximity [56] in the cereal trade are confirmed by this paper. The regional cooperation and degree of regional integration profoundly affect international trade relations, especially in cereal trade [21].…”
Section: Understanding Of Cereal Trade Network Structuressupporting
confidence: 81%
“…This reflects the spatial scale dependence effect of international trade relations [54,55], i.e., that the influence of different levels of network cores is differentiated at the global and regional scales. The characteristics of geographical proximity [56] in the cereal trade are confirmed by this paper. The regional cooperation and degree of regional integration profoundly affect international trade relations, especially in cereal trade [21].…”
Section: Understanding Of Cereal Trade Network Structuressupporting
confidence: 81%
“…The literature review revealed multiple methods of combining individual factors into an overall vulnerability index: (i) further weighting variables [ 17 ], (ii) subjective weights [ 21 ], or (iii) no weights are used [ [18] , [19] , [20] ]. To overcome these methodological shortcomings, we used PCA to determine the weights for combining these individual factors into a standardized IVI, as previously suggested [ 16 , 22 , 23 ].…”
Section: Conceptual Framework Data Bases and Methodsmentioning
confidence: 99%
“…The trade vulnerability of China in the international grain trade has also been assessed [ 19 ]. In the study, the vulnerability index was calculated by dividing a measure of import dependence by a measure of export dependence.…”
Section: Literature Review On Vulnerability Assessmentsmentioning
confidence: 99%
“…Ukraine and Russia are the largest grain exporters in the Belt and Road region, and China should seize the opportunity to strengthen cooperation. Duan (2021) [17] pointed out that there are differences in the dependence on different trading partners in China's current grain trade, that the grain trade shows vulnerability and high spatial and temporal heterogeneity among countries, and that the vulnerability areas are in North America and Northeast Asia with a likelihood of expanding.…”
Section: Related Research 121 Research On Agricultural Product Trade ...mentioning
confidence: 99%